Revitalisasi Kompleks Pasar dan Terminal Sungguminasa Gowa dengan Konsep Bentuk Arsitektur Modern - Allamanda Chatartica M.; Marwati, Marwati; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2023)
The revitalization of the Sungguminasa Market Complex and Terminal Area in Gowa Regency aims to fulfill the wants and needs of the community, especially in Gowa Regency. It is hoped that the rearrangement of the market and terminal area will accommodate the community’s needs due to congestion problems and irregular market space. The combination of markets and terminals supports the activities of the city of Sungguminasa and its surroundings. Descriptive analysis is used with the exploratory design method in finding modern architectural forms that combine terminal and market functions. The design results found that the modern architectural form fits perfectly with the triangular roof shape, and the material is easy to clean and waterproof. Accessibility is an important factor that connects the circulation of activities between terminal and market functions.